Diversity and epidemiology of plant rhabdoviruses - Dietzgen, Ralf Georg (2020)
Plant rhabdoviruses are recognized by their large bacilliform particles and for being able to replicate in both their plant hosts and arthropod vectors. This review highlights selected, better studied examples of plant rhabdoviruses, their genetic diversity, epidemiology and interactions with plant hosts and arthropod vectors: Alfalfa dwarf virus is classified as a cytorhabdovirus, but its multifunctional phosphoprotein is localized to the plant cell nucleus. Lettuce necrotic yellows virus subtypes may differentially interact with their aphid vectors leading to changes in virus population diversity. Interactions of rhabdoviruses that infect rice, maize and other grains are tightly associated with their specific leafhopper and planthopper vectors. Future outbreaks of vector-borne nucleorhabdoviruses may be predicted based on a world distribution map of the insect vectors. The epidemiology of coffee ringspot virus and its Brevipalpus mite vector is illustrated highlighting the symptomatology and biology of a dichorhavirus and potential impacts of climate change on its epidemiology.